KioskAR: An Augmented Reality Game as a New Business Model to Present Artworks. (14th March 2016) - Sekhavat, Yoones A.
Abstract : This paper presents the architecture of KioskAR, which is a pervasive game implemented using augmented reality (AR). This game introduces a new business model that makes it possible for players to present their artworks in virtual kiosks using augmented reality, while they are having fun playing the game. In addition to competition between the players in the game, this game requires social interaction between players to earn more points. A user study is conducted to evaluate the sense of presence and the usability of the application. The results of experiments show that KioskAR can achieve a high level of usability as well as sense of presence.